Physical Self-Concept and Physical Activity Levels between Physical Education Major and Non-Physical Education Major College Students - Gorospe, Joanne; Ferrer, Veronica C. (Technium Social Sciences Journal, 2022)
The study was designed to examine differences in physical self-concept and physical activity between physical education major and non-physical education major college students. Physical self-description and physical activity questionnaires were administered to 161 students. The Physical Self-Description Questionnaire (PSDQ) has 11 factors namely, action, appearance, body fat, coordination, endurance, flexibility, health, sport, strength, global physical, and global esteem. In the main effect, it was found that physical education major and non-physical education major students vary in the levels of their physical self-concept. Physical education majors were found to have higher physical self-concept in terms of action, coordination, endurance, sport, strength, and global esteem. Similarly, the physical education major and non-physical education major students differ in the levels of their physical activity. Among the 11 factors of physical self-concept, sport best predicts the level of physical activity of the students.